2016
DOI: 10.3329/jom.v17i2.30069
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rh alloantibody in Thalassaemia Patients

Abstract: Summary: Thalassaemiais a congenital hemolytic disorder caused by partial or complete deficiency of ? or ? globin chain synthesis. The disease is treated by lifelong red cell transfusion. So they are at high risk of developing allo-antibodies, resulting difficult to obtain compatible blood, results in, haemolysis & occasionally life threatening events.Objectives: To find out the frequency of Rhesus alloantibodies among the thalassaemic patients.Methods: This cross sectional study was done in the department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Another study done in Eastern India evaluating 500 patients with thalassaemia major has shown an incidence of 5.6% in alloimmunization and 1% had auto antibody formation [14]. A study among 100 patients carried out in Bangladesh revealed antibody detection in 6% of patients [15]. A study done in a children's hospital in Philadelphia has revealed that in patients with Sickle cell disease there 58% of tested patients have developed red cell antibodies despite of receiving phenotypically matched blood [16].…”
Section: Discussionmentioning
confidence: 99%
“…Another study done in Eastern India evaluating 500 patients with thalassaemia major has shown an incidence of 5.6% in alloimmunization and 1% had auto antibody formation [14]. A study among 100 patients carried out in Bangladesh revealed antibody detection in 6% of patients [15]. A study done in a children's hospital in Philadelphia has revealed that in patients with Sickle cell disease there 58% of tested patients have developed red cell antibodies despite of receiving phenotypically matched blood [16].…”
Section: Discussionmentioning
confidence: 99%